2021
DOI: 10.3390/plants10091964
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Trichoderma spp. Isolates in Cocoa Seed Treatment and Seedling Production

Abstract: Isolates of Trichoderma spp., a soil fungus, has been used to control diseases and promote plant growth, reducing the use of chemicals in the production of seedlings of different plant species. We evaluated the effect of some Trichoderma spp. isolates on seed treatment and seedling production of Theobroma cacao. Five isolates from the Amazon region were tested. In laboratory, the following variables were evaluated for seed treatments: germination, germination speed index, radicle and hypocotyl lengths, and fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
(40 reference statements)
0
6
0
Order By: Relevance
“…+ Bacillus subtillis) showed better performance reducing the incidence of moniliasis and obtaining the higher fruit weight. De Sousa et al (2021) evaluated five isolated Trichoderma spp., on seed treatment and seedling production of Theobroma cacao and found fungi incidence of 26.5% only in the control treatment, while incidence fungi was 0% for all Trichoderma isolates. Likewise, Seng et al (2014) reported a significant reduction of incidence of monilia infection by 11%.…”
Section: Percentage (%)mentioning
confidence: 99%
“…+ Bacillus subtillis) showed better performance reducing the incidence of moniliasis and obtaining the higher fruit weight. De Sousa et al (2021) evaluated five isolated Trichoderma spp., on seed treatment and seedling production of Theobroma cacao and found fungi incidence of 26.5% only in the control treatment, while incidence fungi was 0% for all Trichoderma isolates. Likewise, Seng et al (2014) reported a significant reduction of incidence of monilia infection by 11%.…”
Section: Percentage (%)mentioning
confidence: 99%
“…For inoculation of Trichoderma spp. in seeds and seedlings, the mass production of the fungi in parboiled rice was made and stored under refrigeration until the preparation of the suspensions for use in the trial [3,5].…”
Section: Obtaining Jabuticaba Seeds and Trichoderma Isolatesmentioning
confidence: 99%
“…The use of beneficial microorganisms, such as Trichoderma, can be applied to stimulate the development of seedlings. In addition to acting as disease control agents in several cultivated species, fungi of this genus are capable of promoting growth and inducing plant resistance to diseases [2][3][4][5][6][7] and resistance to salinity [8], with great environmental and economic importance for agriculture.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of mixtures containing strains communicating with each other to maximise antibiotic production and disease control could be another approach in the improvement of control of soil-borne diseases (Becker et al, 1997;Davelos et al, 2004). According to De Sousa et al (2021), inoculation with Trichoderma increased the length of the radicle and hypocotyl and showed no fungi in the seeds. Some treatments increased the height and the plant root dry mass in seedlings.…”
Section: Biological Seed Treatments (Use Of Antagonists)mentioning
confidence: 99%